A verification of motivations for over-the-top binge and short viewing of audio-visual content. Issue 3 (1st October 2020) - Yoo, Jongsu; Lee, Jieon; Lee, Daeho
ABSTRACT : The current study purposes to verify the motivations for the consumption of audio-visual content through binge-viewing or short watching. It is grounded in the uses and gratification perspective to examine five distinct types of stimuli for binge-viewing and short watching: enjoyment, efficiency, information seeking, social interaction, and relaxation. Results of the analyses demonstrate that enjoyment and efficiency are positively associated with the tendency toward binge-viewing. However, the inclination toward short watching is correlated to enjoyment, efficiency, social interaction, and information seeking, and relaxation was not predictive of either inclination. The study also contemplated loneliness and addiction as moderating variables for binge-viewing and short watching behaviour. Structural equation modelling (SEM) was employed to validate the moderating effects of these two psychological states. The SEM results of the two-group analysis revealed that loneliness and addiction affected motivation and influenced attitudes toward binge-viewing and short watching. The present study is one of the first attempts to verify and compare the media viewing behaviours of binge-watching and short watching. Thus, it can contribute substantially to a more comprehensive scholarly understanding of over-the-top consumption of audio-visual content.